A new reconfigurable multi-band monopole antenna for different wireless applications - Boukarkar, Abdelheq; Xian Qi Lin; Yuan Jiang (2015 IEEE International Conference on Communication Software and Networks (ICCSN), 2015)
A new compact reconfigurable multi-band monopole antenna for different wireless applications is proposed. The antenna can be reconfigurable using two switches S 1 and S 2 modeled as perfect conductors when their states are on. The states of the switches allow the antenna to have distinct resonant frequencies. The antenna is fabricated and tested. Good agreement between simulated and measured return loss is obtained. The antenna has a simple structure, small size, and can cover several frequency bands by using just two switches; making it distinguishable and suitable for some wireless applications.